2020
DOI: 10.3233/cbm-190609
|View full text |Cite
|
Sign up to set email alerts
|

Serum Matrix metalloproteinase-9 (MMP-9) can help identify patients with papillary thyroid cancer at high risk of persistent disease: Value and limitations of a potential marker of neoplasia

Abstract: BACKGROUND: Matrix metalloproteinase-9 (MMP-9) is an important mediator of invasion and metastasis in neoplasia. In thyroid cancer expression levels correlate with aggressiveness but data on peripheral MMP-9 levels are less definitive. OBJECTIVE: Prospective study evaluating serum MMP-9 in the diagnosis and prognosis of papillary thyroid cancer. METHODS: Serum samples of MMP-9 were drawn before surgery in 185 consecutively enrolled patients with nodular thyroid disease, stratified on pathology as benign diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Our network meta-analysis of six studies (418 PTC patients, 221 benign diseases, 121 controls) using frequentist methods found that patients with PTC had significantly increased serum/plasma MMP9 versus both benign disease (SMD: 3.19, 95% CI: 2.84-3.55) and healthy controls (SMD: 3.13, 95% CI: 2.76-3.50) (Figure 11B). However, serum MMP9 levels were not different between benign and malignant pathology in two studies [73,76], highlighting the need to account for confounders. Data on circulating miR-145 levels in TC patients is limited, representing an area requiring further investigation.…”
Section: Mmp9 and Mir-145 Expression In Thyroid Cancermentioning
confidence: 86%
See 2 more Smart Citations
“…Our network meta-analysis of six studies (418 PTC patients, 221 benign diseases, 121 controls) using frequentist methods found that patients with PTC had significantly increased serum/plasma MMP9 versus both benign disease (SMD: 3.19, 95% CI: 2.84-3.55) and healthy controls (SMD: 3.13, 95% CI: 2.76-3.50) (Figure 11B). However, serum MMP9 levels were not different between benign and malignant pathology in two studies [73,76], highlighting the need to account for confounders. Data on circulating miR-145 levels in TC patients is limited, representing an area requiring further investigation.…”
Section: Mmp9 and Mir-145 Expression In Thyroid Cancermentioning
confidence: 86%
“…Data on circulating miR-145 levels in TC patients is limited, representing an area requiring further investigation. In addition to tissue samples, several studies analyzed MMP9 levels in body fluids of thyroid cancer patients [65,[72][73][74][75][76]. Multiple studies have reported significantly higher serum/plasma MMP9 levels in PTC patients than those with benign thyroid diseases and healthy controls.…”
Section: Mmp9 and Mir-145 Expression In Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…4. The study uses serums as samples, which may provide different results from plasma samples because of coagulants and anticoagulants [106].…”
Section: Mmp-9 Expression Levels In Thyroid Carcinomamentioning
confidence: 99%
“…Serum MMP-9 levels measured using an immunometric assay were evaluated in subjects with PTC in a case-control study that concluded that although serum MMP-9 is not helpful in the diagnosis of PTC, a high pre-surgical level might be a prognostic factor that could dictate the treatment aggressiveness [ 60 ]. In a recent study that investigated the role of MMP-9 promoter −1562C/T functional SNP in the risk of developing PTC, the T allele was found significantly more frequently in subjects with PTC (17.5% vs. 10.1%, p = 0.019) [ 61 ].…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%